Detection limits of tidal-wetland sequences to identify variable rupture modes of megathrust earthquakes. (15th October 2016) - Shennan, Ian; Garrett, Ed; Barlow, Natasha
Abstract: Recent paleoseismological studies question whether segment boundaries identified for 20th and 21st century great, >M8, earthquakes persist through multiple earthquake cycles or whether smaller segments with different boundaries rupture and cause significant hazards. The smaller segments may include some currently slipping rather than locked. In this review, we outline general principles regarding indicators of relative sea-level change in tidal wetlands and the conditions in which paleoseismic indicators must be distinct from those resulting from non-seismic processes. We present new evidence from sites across southcentral Alaska to illustrate different detection limits of paleoseismic indicators and consider alternative interpretations for marsh submergence and emergence. We compare predictions of coseismic uplift and subsidence derived from geophysical models of earthquakes with different rupture modes. The spatial patterns of agreement and misfits between model predictions and quantitative reconstructions of coseismic submergence and emergence suggest that no earthquake within the last 4000 years had a pattern of rupture the same as the Mw 9.2 Alaska earthquake in 1964. From the Alaska examples and research from other subduction zones we suggest that If we want to understand whether a megathrust ruptures in segments of variable length in different earthquakes, we need to be site-specific as to what sort of geological-based criteria eliminate the possibility of a particular rupture mode in different earthquakes. We conclude that coastal paleoseismological studies benefit from a methodological framework that employs rigorous evaluation of five essential criteria and a sixth which may be very robust but only occur at some sites: 1 – lateral extent of peat-mud or mud-peat couplets with sharp contacts; 2 – suddenness of submergence or emergence, and replicated within each site; 3 – amount of vertical motion, quantified with 95% error terms and replicated within each site; 4 – syncroneity of submergence and emergence based on statistical age modelling; 5 – spatial pattern of submergence and emergence; 6 – possible additional evidence, such as evidence of a tsunami or liquefaction concurrent with submergence or emergence. We suggest that it is possible to consider detection limits as low as 0.1–0.2 m coseismic vertical change. Highlights: Revised methodological framework of 6 criteria for coastal paleoseismic studies. New evidence from southcentral Alaska to illustrate different detection limits. No earthquake within last 4000 years had same rupture pattern as 1964 earthquake. Possible to consider detection limits of 0.1–0.2 m of coseismic land-level change.